The Increase of Student Learning Interest through the Application of Recitation Methods Assisted by Cyber Counseling Media - Deliati Deliati; Gusman Lesmana (BIRCU, 2019)
Research data were analyzed through reflective studies in each cycle. The results of data analysis shows that in the first cycle there had been an increase in students learning interest with a success percentage of 38.10% compared with students learning interest before being given action in the first cycle (23.91% of students were successful). However, in this cycle there are still some shortcomings because most students are not familiar with the learning conditions through the recitation method. The shortcomings in the first cycle are seen from the low level of students learning interest in the learning process with an average percentage of 67.26%, lecturer activities 75.05%, and the ability of students with an average score of 71.90 with a success percentage of 54, 35%. In the second cycle, student learning interest and the way lecturers teaching is run better. The activity of students and lecturers in learning has increased with a percentage score of 71.88% and 83.77%, with a graduation rate of 58.70%. Student mastery of the material also increased with an average score of 74.40%. The implementation of the third cycle starts from the problem at the stage of action II. The average score of students' ability to mastery of the material obtained in action III is 85.83, with a graduation rate of 91.30%. The average score of student activities in PBM is 78.80%. Meanwhile, lecturers' activities in learning also improved well, with a percentage of 87.70%.